P.R209H GH1 variant challenges short stature assessment. (February 2020) - Sanguineti, Nora; Braslavsky, Debora; Scaglia, Paula A.; Keselman, Ana; Ballerini, Maria G.; Ropelato, Maria G.; Suco, Sofia; Vishnopolska, Sebastian; Berenstein, Ariel J.; Jasper, Héctor; Domené, Horacio M.; Rey, Rodolfo A.; et al.
Abstract: Objective: to describe the marked variability in clinical and biochemical patterns that are associated with a p.R209H GH1 missense variant in a large Argentinean pedigree, which makes the diagnosis of GHD elusive. Design: We describe a non-consanguineous pedigree composed by several individuals with short stature, including 2 pediatric patients with typical diagnosis of isolated growth hormone deficiency (IGHD) and 4 other siblings with severe short stature, low serum IGF-1 and IGFBP-3, but normal stimulated GH levels, suggesting growth hormone insensitivity (GHI) in the latter group. Results: Patients with classical IGHD phenotype carried a heterozygous variant in GH1 : c.626G>A (p.R209H). Data from the extended pedigree suggested GH1 as the initial candidate gene, which showed the same pathogenic heterozygous GH1 variant in the four siblings with short stature and a biochemical pattern of GHI. Conclusions: We suggest considering GH1 sequencing in children with short stature associated to low IGF-1 and IGFBP-3 serum levels, even in the context of normal response to growth hormone provocative testing (GHPT). Highlights: Growth hormone provocative tests have many limitations. Phenotype between GHD and GHI may overlap. Genetic evaluation is an additional tool towards a definitive diagnosis of GHD. GH1 p.R209H variant has markedly variable clinical and biochemical consequences. It is advisable to explore GH1 in short children with low IGF-I and IGFBP-3, despite normal GHPT.